PENYULUHAN HUKUM: PENINGKATAN PEMAHAMAN MASYARAKAT MENGENAI PENDAFTARAN TANAH SEBAGAI UPAYA MEWUJUDKAN REFORMA AGRARIA: Legal Counseling: Increasing Public Understanding Regarding Land Registration as an Effort to Achieve Agrarian Reform - Akbar, Muhammad; Subroto, Aryo; Putri, Yunita; wulandari , Jessi aprilia; Seven Jon, Joya Marcyella (Program Studi Sastra Indonesia Universitas Mulawarman, 2024)
Abstract: The Complete Systematic Land Registration (PTSL) is one of the programs for Agrarian Reform by accelerating the legalization of land rights. However, in practice there are still incomplete document requirements associated with a lack of understanding by the community regarding the program and the importance of certificates of ownership in physical possession ofland parcels. Therefore, it is necessary to carry out counselling to increase legal understanding for the community regarding theurgency of land registration through the PTSL program and maintenance of land data. The method used in this activity was counselling which was carried out through two stages, namely the arrest of sub-districts and neighborhood associations participatingin PTSL and socialization and material interventions related to PTSL. In order to obtain an increase in legal understanding for people who take part in the PTSL program in the thirty-two, forty-one and forty-eight neighborhoods of the Manggar Baru Village. Keywords: PTSL; Agrarian Reform; Counselling Abstrak: Pendaftaran Tanah Sistematis Lengkap (PTSL) adalah salah satu program Reforma Agraria dengan cara melakukakan upaya percepatan legalisasi hak atas tanah. Akan tetapi, dalam implementasinya kerap kali masih terjadi ketidaklengkapan dokumen persyaratan yang didasari atas kurang pahamnya masyarakat terkait dengan program dan pentingnya surat pernyataan penguasaanfisik bidang tanah. Olehnya itu, perlu dilakukan penyuluhan untuk meningkatkan pemahaman hukum bagi masyarakat terkait urgensi pendaftaran tanah melalui program PTSL dan pemeliharaan data tanah. Metode yang digunakan adalah penyuluhan. Penyuluhan dilakukan dengan dua tahapan yaitu pemetaan kelurahan dan Rukun Tetangga (RT) yang mengikuti program PTSL dansosialisasi serta penyampaian materi terkait program PTSL. Hasilnya diperoleh peningkatan pemahaman hukum bagi masyarakat yang mengikuti program PTSL di RT 32, 41 dan 48 Kelurahan Manggar Baru. Kata kunci: PTSL; Reforma Agraria; Penyuluhan